2014
DOI: 10.1088/0004-637x/794/2/126
|View full text |Cite
|
Sign up to set email alerts
|

Is the Ultra-High Energy Cosmic-Ray Excess Observed by the Telescope Array Correlated With Icecube Neutrinos?

Abstract: The Telescope Array (TA) has observed a statistically significant excess in cosmic-rays with energies above 57 EeV in a region of approximately 1150 square degrees centered on coordinates (R.A. = 146.7, Dec. = 43.2). We note that the location of this excess correlates with two of the 28 extraterrestrial neutrinos recently observed by IceCube. The overlap between the two IceCube neutrinos and the TA excess is statistically significant at the 2σ level. Furthermore, the spectrum and intensity of the IceCube neutr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 50 publications
(45 reference statements)
0
35
0
Order By: Relevance
“…An alternative method to search for UHECR sources are correlation studies. Several studies have shown that the distribution of the TA hotspot events is consistent with the hypothesis of a single source, the nearby starburst galaxy M82 being a promising candidate [371,372]. The recent analysis [370] of the PAO data showed evidence for a correlation of the arrival directions of UHECRs with starburst galaxies, i.e.…”
Section: Anisotropiesmentioning
confidence: 52%
“…An alternative method to search for UHECR sources are correlation studies. Several studies have shown that the distribution of the TA hotspot events is consistent with the hypothesis of a single source, the nearby starburst galaxy M82 being a promising candidate [371,372]. The recent analysis [370] of the PAO data showed evidence for a correlation of the arrival directions of UHECRs with starburst galaxies, i.e.…”
Section: Anisotropiesmentioning
confidence: 52%
“…The remaining half are at higher Galactic latitude. Hence both Galactic (e.g., Fox, Kashiyama, & Mészarós 2013;Taylor, Gabici, & Aharonian 2014) as well as extragalactic (e.g., Murase, Inoue, & Dermer 2014;Fang et al 2014) scenarios provide valid explanations for the IceCube detections.…”
Section: Introductionmentioning
confidence: 97%
“…The observed flux in the hotspot [18] . Therefore, a GRB with an extremely high kinetic energy at a distance ∼ Mpc could produce the observed hotspot.…”
mentioning
confidence: 94%